PENGEMBANGAN MEDIA PEMBELAJARAN MULTIMEDIA INTERAKTIF UNTUK MENINGKATKAN MINAT DAN HASIL BELAJAR PESERTA DIDIK PADA PELAJARAN PENDIDIKAN KEWARGANEGARAAN : Studi Research and Development Di SMP Pasundan 1 Bandung - Dharma, Surya (2012)
The importance of learning innovation particularly in Civic Education by using element of technology through the development of interactive multimedia learning media, is one of appropriate strategy to enhance students' interest and learning outcome. By this interactive multimedia learning media, it is hoped that Civic Education subject is become powerful and meaningful subject for students. This research and development is back grounded by students' learning outcome and interest which is low in Civic Education subject in SMP Pasundan 1 Bandung. This is because teacher and student interaction take advantage less learning media. The aim of this study is generate interactive multimedia learning media to be able to enhance students' interest and learning outcome in Civic Education lesson of class VII in SMP Pasundan 1 Bandung. To achieve that aim, researcher use research and development (R&D) approach, Borg and Gall. In particular, the aim of this study are: (1) describe Civic Education learning condition in SMP Pasundan 1 Bandung, (2) obtain the description how to develop interactive multimedia learning media conceptually, (3) obtain the description how to implement interactive multimedia learning media conceptually, (4) find out whether there is enhancement of students' learning interest in Civic Education lesson after the use of interactive multimedia learning media. Result of study show that (1) Civic Education learning in SMP Pasundan 1 Bandung is conservative because teacher still use media of learning which is less varied, (2) development stages of interactive multimedia learning media are needed which consist of pre production, production and post production stages, (3) teacher and student's computer basic ability in using interactive multimedia learning and interactive multimedia learning media can be used organized with computer laboratory, classically in class, or can be used by students out of school by needing some facility or equipment such as computer and the like, LCD Projector, and some another supporting equipment, (4) there is significant difference between pretest and posttest result in students' learning interest after using interactive multimedia learning media, (5) there is significant difference between pretest and posttest result in students' Civic Education learning outcome after using interactive multimedia learning media. Therefore, this result of study recommend that interactive multimedia learning media can be used as one of learning media to enhance students' learning outcome and interest in Civic Education lesson.